OP0121 Enbrel® (etanercept) vs. methotrexate (mtx) in early rheumatoid arthritis (era trial): two-year follow-up. (1st June 2001) - Genovese, M; Martin, RW; Fleischmann, R; Keystone, E; Bathon, J; Spencer-Green, G; Finck, B
Abstract : Background: The first year of this 2-year study of patients with early erosive RA (mean disease duration 1 year) demonstrated that ENBREL 25 mg twice weekly gave a more rapid clinical response and was more effective in preventing erosions than high dose (median 20 mg/wk) oral MTX. 1 Objectives: To evaluate safety, clinical improvement, and radiographic outcomes in patients receiving ENBREL or MTX for up to 2 years. Methods: Patients enrolled in this 2-year study continued to receive the therapy to which they had been randomised in an open-label fashion after the study was unblinded (at a mean of 17.3 months). The 2-year endpoints were ACR responses (using last on-drug observation carried forward analyses) and change in Sharp score. Readers were blinded to treatment and chronological order of the x-rays. All 632 patients were included in the analyses. Results: 154 of 207 patients (74%) who received ENBREL 25 mg completed 2 years of treatment, compared to 129 of 217 patients (59%) who received MTX. Twice as many patients (12%) discontinued MTX for adverse events as did those taking ENBREL. The ACR 20 response at 2 years was 72% in those randomised to ENBREL and 59% in those randomised to MTX (P = 0.005). Radiographic evaluations demonstrated that ENBREL 25 mg was superior to MTX in arresting radiographic progression over the 2-year period. Mean (median) changes in total Sharp score were 1.3 (0) and 3.2 (0.5) units in the ENBREL 25 mg and MTX groups, respectively (P = 0.001) and changes in erosion score were 0.7 (0) and 1.9 (0) units, respectively (P = 0.001). ENBREL 25 mg prevented radiographic progression in 63% of patients, compared to 51% of MTX patients who did not progress (P = 0.017). ENBREL 25 mg was also superior to the 10 mg dose in inhibiting radiographic progression. Significantly more ENBREL 25 mg patients than MTX patients had a clinically meaningful (at least 0.5 units) improvement from baseline in HAQ disability score. ENBREL continued to be well tolerated with over 2 years of exposure. Conclusion: This 2-year study demonstrated that ENBREL was superior to MTX in reducing clinical signs and symptoms of RA and inhibiting radiographic progression. Reference: Bathon JM, Martin RW, Fleischmann RM, et al . NEJM 2000;343:1586–93